Genetic diversity of human metapneumovirus (Pneumoviridae: Metapneumovirus) in Russia: results of molecular analysis - Artem V. Fadeev; Yan V. Ivanov; Polina A. Petrova; Alexander A. Perederiy; Maria M. Pisareva; Alexey D. Moshkin; Andrey B. Komissarov; Daria M. Danilenko; Dmitriy A. Lioznov (Вопросы вирусологии, 2025)
Introduction. Human metapneumovirus (hMPV) holds significant epidemiological importance, being a dominant cause of lower respiratory tract infections in children under two years of age and individuals over 65. Multiple infections with hMPV throughout a person’s life are possible due to the antigenic and genetic variability of the virus. However, the genetic variability of hMPV circulating in Russia remains unexplored.